An 8‐channel receive array for improved 31P MRSI of the whole brain at 3T. Issue 2 (21st March 2019) - van Uden, Mark J.; Peeters, Tom H.; Rijpma, Anne; Rodgers, Christopher T.; Heerschap, Arend; Scheenen, Tom W. J.
Abstract : Purpose: To demonstrate a 1 H/ 31 P whole human brain volume coil configuration for 3 Tesla with separate 31 P transmit and receive components that maintains 1 H MRS performance and delivers optimal 31 P MRSI with 1 H decoupling. Methods: We developed an 8‐channel 31 P receive array coil covering the head to be used as an insert for a commercial double‐tuned 1 H/ 31 P birdcage transmit‐receive coil. This retains the possibility of using low‐power rectangular pulses for 1 H‐decoupled 3D 31 P MRSI (nominal resolution 17.6 cm 3 ; acquisition duration 13 min) but increases the SNR with the receive sensitivity of 31 P surface coils. The performance of the combined coil setup was evaluated by measuring 1 H and 31 P SNR with and without the 31 P receive array and by assessing the effect of the receive array on the transmit efficiencies of the birdcage coil. Results: Compared to the birdcage coil alone, the 31 P insert in combination with the birdcage achieved an average 31 P SNR gain of 1.4 ± 0.4 in a center partition of the brain. The insert did not cause losses in 1 H MRS performance and transmit efficiency, whereas for 31 P approximately 20% more power was needed to achieve the same γB1. Conclusion: The new coil configuration allows 1 H MRSI and optimal 1 H‐decoupled 3D 31 P MRSI, with increased SNR of the human brain without patient repositioning, for clinical and research purposes at 3 Tesla.